ANALISIS SISTEM INFORMASI AKUNTANSI TERHADAP PROSEDUR PENAGIHAN PIUTANG CUSTOMER PT. VIOLET INDONESIA - Siti Wardah Noorusyiam; Dinda Tri Ayuning Tyas; M.F. Hidayatullah (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Finding out how the customer debt collection process works at PT. Violet Indonesia is the main reason for this study. This research makes use of an approach that involves analysing both descriptive and qualitative data. The material required to examine the connection between accounting information systems and debt collection is derived from a mix of in-depth interviews and references to pertinent journals and publications. Steps in acquiring data and forming judgements later. Research on PT. Violet Indonesia found that their accounting information system is useful for collecting customer debts. The accounting information system mandates the manual execution of the debt collection method using Microsoft Excel